Disney's Final Package Film: The Making and Marketing of The Adventures of Ichabod and Mr. Toad (1949). (July 2019) - Neuman, Robert
As the last of Disney's package films in the troubled decade of the 1940s, The Adventures of Ichabod and Mr. Toad (1949) has acquired the reputation of an awkward 'marriage of convenience' of two separate stories based on well-known literary properties, one American and one British: Washington Irving's The Legend of Sleepy Hollow and Kenneth Grahame's The Wind in the Willows . This article, by reconstructing the gestation of the film over eight years, demonstrates the degree to which the stark contrast between the two halves was not only inevitable but deliberate. This is especially visible in the handling of the narrative – action set pieces for Toad and a full-fledged musical for Ichabod – as well as the art direction, which favors realism for Toad and stylization for Ichabod . An analysis of the marketing campaign shows that the film was presented as a facsimile of the standard double bill of the period, with an A picture and a B picture. In lauding its new cast of sympathetic Disney characters and stories that stimulate a full range of emotional responses, some film critics in Britain and the US compared Ichabod and Mr. Toad favorably to Snow White and the Seven Dwarfs, Dumbo and the Silly Symphonies, calling the film a harbinger of a Disney renaissance – a revival that would be fully realized with the premiere of Cinderella in 1950.